Influence of Online Customer Review and Online Customer Rating On Purchasing Decision on Shopee E-Commerce: Study on Management Study Program Students, Faculty of Economics and Business, Makassar State University - Natasya, Wilda Dwitya Putri; Musa, Muhammad Ichwan; Haeruddin, Muhammad Ilham Wardhana; Hasbiah, Siti; Aslam, Nurul Fadilah (Journal of Business Management and Economic Development, 2024)
This research is a quantitative study that aims to find out influence of online customer review and online customer rating on purchasing decision on shopee e-commerce (study on Management study program students of the Faculty of Economics and Business of Makassar State University). The independent variables in this study are online customer review and online customer rating, while the dependent variable is Purchasing Decision. The population in this study is active students Management study program of the Faculty of Economics and Business of Makassar State University class of 2020-2022. Sampling using purposive sampling technique and obtained a total sample of 100 respondents. Data collection techniques used are questionnaires and literature study. The data analysis technique used is multiple linear regression analysis using SPSS V.21. The results of this study indicate that online customer review (X1) partially has a significant effect on purchasing decision on shopee e-commerce, online customer rating (X2) partially has a significant effect on purchasing decision on shopee e-commerce, and online customer review (X1) and online customer rating (X2) simultaneously have a significant effect on purchasing decision on shopee e-commerce.